Lost in Transit: Long-Distance Trafficking and Phloem Unloading of Protein Signals in Arabidopsis Homografts - Paultre, Danae Simone Genevieve (Plant Cell, 2016)
In addition to moving sugars and nutrients, the phloem transports many macromolecules. While grafting and aphid stylectomy experiments have identified many macromolecules that move in the phloem, the functional significance of phloem transport of these remains unclear. To gain insight into protein trafficking, we micrografted Arabidopsis thaliana scions expressing GFP-tagged chloroplast transit peptides under the 35S promoter onto nontransgenic rootstocks. We found that plastids in the root tip became fluorescent 10 d after grafting. We obtained identical results with the companion cell-specific promoter SUC2 and with signals that target proteins to peroxisomes, actin, and the nucleus. We were unable to detect the respective mRNAs in the rootstock, indicating extensive movement of proteins in the phloem. Outward movement from the root protophloem was restricted to the pericycle-endodermis boundary, identifying plasmodesmata at this interface as control points in the exchange of macromolecules between stele and cortex. Intriguingly, signals directing proteins to the endoplasmic reticulum and Golgi apparatus from membrane-bound ribosomes were not translocated to the root. It appears that many organelle-targeting sequences are insufficient to prevent the loss of their proteins into the translocation stream. Thus, nonspecific loss of proteins from companion cells to sieve elements may explain the plethora of macromolecules identified in phloem sap.